Mindfulness as A Strategy for Emotion Regulation in Fatherless Adolescents - Ardianti Agustin; Firsty Oktaria Grahani; Aironi Zuroida; M.Reza Rahmadian; Vidi Yuliana Sari (Psikostudia : Jurnal Psikologi, 2026)
Adolescents experiencing father absence (fatherless) are vulnerable to difficulties in managing emotions and have a higher risk of mental health disorders, such as anxiety and depression, due to the loss of a significant figure in the emotional learning process. Mindfulness refers to non-judgmental awareness of present-moment experiences that serves as a protective factor in helping individuals manage emotions adaptively. This study aims to examine the effect of mindfulness on emotion regulation among fatherless adolescents. A quantitative approach with a correlational design was applied to 100 fatherless adolescents aged 15–18 years selected through purposive sampling technique with the criteria of not living with their biological father for at least the past three years. Data were collected using the Mindful Attention Awareness Scale (MAAS) and the Emotion Regulation Questionnaire (ERQ). Simple linear regression analysis using IBM SPSS Statistics version 25 showed that mindfulness had a positive and significant effect on emotion regulation (p < 0.05; R² = 0.310), with an effective contribution of 31%. These findings confirm mindfulness as a protective factor that strengthens the ability of fatherless adolescents to manage emotions adaptively. The implications of this research recommend the integration of mindfulness-based interventions in school counseling services and social assistance programs, as well as encourage longitudinal research to examine the effectiveness of such interventions and explore other factors contributing to emotion regulation in this vulnerable population.